THE EFFECT OF FINANCIAL LITERACY AND HEDONISTIC LIFESTYLE ON PAYLATER FINANCIAL MANAGEMENT BEHAVIOR: THE MEDIATING ROLE OF SELF-CONTROL - Ade Nurohmah; Mardiyani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This research is motivated by the increasing use of payLater among young people in theCirebon region, which has the potential to lead to the risk of default due to less controlled financial management behavior. The purpose of this study is to analyze the influence of financial literacy and a hedonistic lifestyle on financial management behavior, with self-control as a mediating variable. The research method used is a quantitative method with a causal associative approach. The sampling technique used was purposive sampling with 120 selected respondents who met the criteria. Data analysis using SmartPLS 4.0. The research results indicate that financial literacy significantly influences financial management behavior and self-control. Meanwhile, a hedonistic lifestyle does not significantly affect financial management behavior but significantly impacts self-control. Additionally, self-control is proven to significantly mediate the influence of financial literacy and a hedonistic lifestyle on financial management behavior.